Two new species of Atlantoscia Ferrara & Taiti, 1981 (Isopoda: Oniscidea: Philosciidae) from southern Brazil described in the light of integrative taxonomy - Zimmermann, Bianca Laís; Campos-Filho, Ivanklin Soares; Cardoso, Giovanna Monticelli; Santos, Sandro; Aguiar, José Otávio; Araujo, Paula Beatriz (Zootaxa, 2018)
The use of molecular data in association with classical taxonomy has helped to alleviate the taxonomic impediment through the discovery, delimitation and description of new species. Terrestrial isopods are the largest suborder of Isopoda; however, there are very few active taxonomists in this group and a representative part of the terrestrial isopods world diversity remains unexplored. The genus Atlantoscia comprises five species in which diagnostic characters are few and show subtle differences among the species. The objective of this study was to delimit and describe two new species of the genus Atlantoscia from southern Brazil by using traditional taxonomy coupled with genetic information. Specimens were analyzed morphologically and by the aid of two molecular markers, mitochondrial COI and nuclear 18S rRNA. The validity of the new species Atlantoscia antennamaculata sp. nov. and Atlantoscia australis sp. nov. was corroborated, unambiguously, by morphological approach, phylogenetic analysis and species delimitation methods. Our study reinforces the fact that, despite the undeniable importance of comparative morphology in species discovery, new methods and data, particularly molecular ones, are becoming prominent and an integrative part of the taxonomy practice.